PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA BAGI KINERJA PEGAWAI (Studi Pada Dinas Pemadam Kebakaran Kota Semarang) - Dina Puji Lestari, 15.05.51.0137; Priyono, Bambang Suko (Students' Journal of Economic and Management, 2019)
The purpose of this study was to examine the effect of leadership and work motivation on job satisfaction and its impact on employee performance. This research was conducted at the Semarang City Fire Department. Method of sampling using saturated samples or census. The relationship and or influence between variables is explained by using multiple regression analysis. The results showed that leadership had a significant positive effect on job satisfaction. Motivation has a positive and significant effect on job satisfaction. Leadership has a positive and significant effect on employee performance. Motivation has a significant positive effect on employee performance. Job satisfaction has a significant positive effect on employee performance. Satisfaction variables have not been able to mediate leadership on performance because the direct influence is greater than indirect influence. The satisfaction variable has not been able to mediate the effect of motivation on performance because the direct influence is greater than the indirect effect.